OKTATÁSI, NEVELÉSI TRENDEK ÉS MÓDSZEREK A DIGITÁLIS KULTÚRÁBAN - Haffner-Kiss, Alexandra (Kultúratudományi Szemle, 2025)
Educational trends and methods in the field of digital culture The study aims to show the impact of online time on the digital generation. Members of the alpha generation spend as much time online as they do in school. This level of daily activity has become inescapable for educational researchers. Several hours of daily and even simultaneous use of smart devices can impact students and change their learning habits. Online platforms are increasingly dominated by visual and video material, affecting how students process information. Nowadays, the battle for users' attention on social networking sites has become commonplace, with a rapidly changing visual and audio experience based on multiple stimuli. Presumably, the learning habits of members of the alpha generation reflect this need. In the study, the researcher analyses the effects of online space on socialisation and text comprehension processes.